Aortic aneurysms' treatment with endovascular stent-graft - Rahman, Ali; Colak, Mehmet Cengiz; Ozdemir, Huseyin; Ozguler, Murat; Cil, Barbaros E. (Baycinar Medical Publ-Baycinar Tibbi Yayincilik, 2009)
Background: The aim of this study was to investigate the efficacy of treatment with endovascular stent-graft in thoracal and abdominal aortic aneurysms. Methods: In 2007, one thoracic and six abdominal lesions (7 males; mean age 75.8 years; range 65 to 94 years) were treated with endovascular stent-graft. The indication for endovascular repair was nonspecific degenerative aneurysm. In all patients Medtronic (R) Talent stent-graft was used. Results: Repair was performed with thoracic stent-graft (n=1), aorto-biiliac stent-graft together with left iliac stent-graft (n=1), and only aorto-biiliac stent-grafts (n=5). Technical success rate was 100%. No mortality, major complication or need of immediate conversion to open repair was seen. One patient died during the early follow-up period. No mortality due to graft infection or aneurysm rupture was detected. Conclusion: In selected patients endovascular treatment of aortic lesions by using stent-graft is a method with a high degree of technical success and a low morbidity and mortality rate in the early period.
Keywords: Aorta aneurysm; computed tomography; endovascular aortic repair